Renewable sugars from oil palm waste - Hassan, Mohd Ali; Ariffin, Hidayah; Mohd Zahari, Mior Ahmad Khushairi; Zakaria @ Mamat, Mohd Rafein; Salihon, Jailani; Mokhtar, Mohd Noriznan; Shirai, Yoshito (2012)
The invention provides method for producing sugars from oil palm fronds wherein the steps comprises of (1) extracting oil palm frond juice from the oil palm fronds; and (2) treating the oil palm frond juice. The invention also provides a method of using the said oil palm frond juice for producing polyhydroxyalkanoates such as polymer of hydroxyalkanoic acid, hydroxybutyric acid, hydroxyvaleric acid, and a copolymer thereof, wherein the copolymers maybe poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV), poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (P3HB4HB), polymers and/or copolymers of hydroxyterminated polyhydroxybutyrate (PHB-OH), heteropolymers thereof and any other polymers. In addition to that, biofuels and organic acids such as bioethanol, biobutanol, lactic acid, succinic acid, and all products that can be produced through chemical and biological synthesis from these sugars from the OPF juice. The present invention also provides a method for producing polyhydroxyalkanoate (PHA) by incubating at least one strain of PHA-producing microorganisms in a culture medium comprising of sugars and/or a derivative thereof from the oil palm frond juice. The microorganisms used can be of bacteria, mold or yeast from the group Azotobacter, Pseudomonas, Coliform, Alcaligenes, Bacillus, Lactobacillus and genetically modified form thereof preferably Azotobacter chroococcum, recombinant Escherichia coli, Alcaligenes latus, Pseudomonas oleovorans and Cupriavidus necator.